A invenção da florestania: a participação da mídia acreana na construção de um novo discurso ideológico - Pinheiro, Francisco de Moura (2013)
This research investigates the construction of a new ideology in the state of Acre, in the middle of the twenty-first century, waged by a coalition of political groups called Popular Front, this coalition composed of the following parties: Workers Party (PT), Brazilian Communist Party (PCB), Communist Party of Brazil (PC do B), Green Party (PV) and the Democratic Labor Party (PDT). The new ideology, based on the issue of sustainable development, established as a nodal point of his speech the word "florestania", combination of the words "forest" and "citizenship." For the new ideology could be disseminated and therefore sedimented between Acre population, the Popular Front strategy was to invest heavily in the local media. This research wants to answer the following questions: When does the florestania emerged in Acre? The hegemonic discourse which countered the florestania? How the theme florestania was reported in the media of Acre? What were the main contracts announced proposed in radio, television and Acre newspapers? What is the relationship between sustainable development and florestania? Also, the research wants to emphasize the concepts of ideology, scheduling and communicative action through relevant theories, adapting them to the object of the proposed study. The corpus includes the period 1999 to 2006, consists of pieces aired on Aldeia TV, Aldeia Radio and newspaper articles published on Página 20, in Rio Branco, capital of Acre, and maintained by the State Government. As a theoretical framework will be used to Critical Social Theory, from the concepts worked by John B. Thompson, the hypothesis of Agenda Setting, based on Mauro Wolf; Discourse Analysis, from Norman Fairclough, the Theory of Ideology, supported by Ernesto Laclau, and the Ecology of Knowledge, as Boaventura de Sousa Santos. The research is centered discursive examination of documents and interviews about florestania, with the qualitative method as the basis for data collection. We conducted interviews with characters related to the subject, as well as documentary analysis. The content presented by broadcasters and newspaper chosen for the research are examined with emphasis on discourse analysis, looking up the bases for the contracts or underlying communication